Aphasia or Neglect after Thalamic Stroke: The Various Ways They may be Related to Cortical Hypoperfusion - Sebastian, Rajani; Schein, Mara G.; Davis, Cameron; Gomez, Yessenia; Newhart, Melissa; Oishi, Kenichi; Hillis, Argye E. (Frontiers in Neurology, 2014)
Although aphasia and hemispatial neglect are classically labeled as cortical deficits, language deficits or hemispatial neglect following lesions to subcortical regions have been reported in many studies. However, whether or not aphasia and hemispatial neglect can be caused by subcortical lesions alone has been a matter of controversy. It has been previously shown that most cases of aphasia or hemispatial neglect due to acute non-thalamic subcortical infarcts can be accounted for by concurrent cortical hypoperfusion due to arterial stenosis or occlusion, reversible by restoring blood flow to the cortex. In this study we evaluated whether aphasia or neglect occur after acute thalamic infarct without cortical hypoperfusion due to arterial stenosis or occlusion. Twenty patients with isolated acute thalamic infarcts (10 right and 10 left) underwent MRI scanning and detailed cognitive testing. Results revealed that 5/10 patients with left thalamic infarcts had aphasia and only 1 had cortical hypoperfusion, whereas 2/10 patients with right thalamic infarcts had hemispatial neglect and both had cortical hypoperfusion. These findings indicate that aphasia was observed in some cases of isolated left thalamic infarcts without cortical hypoerfusion due to arterial stenosis or occlusion (measured with time to peak delays), but neglect occurred after isolated right thalamic infarcts only when there was cortical hypoperfusion due to arterial stenosis or occlusion. Therefore, neglect after acute right thalamic infarct should trigger evaluation for cortical hypoperfusion that might improve with restoration of blood flow. Further investigation in a larger group of patients and with other imaging modalities is warranted to confirm these findings.